(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the artistic expression of soul-body, soul-love relations used in the poetry of the great poet Alisher Navoi. The ideas advanced through the concepts of soul, spirit, body, love, and lust are analyzed.